550 An international comparison of the efficacy of regulatory mechanisms regarding traditional medicines (TM) - Esther Chung; Terry Church (Journal of Clinical and Translational Science)
Objectives/Goals: To identify the most impactful regulations regarding the approval and marketing of TMs in the U.S., E.U., Japan, Australia, China, and India enacted between the years 2000 and 2022. To explore TM-related regulations in new countries, Japan and Australia, for their novel regulatory approaches in intersecting Western and Eastern medical practices. Methods/Study Population: International regulatory bodies included in this study were chosen based on the country’s long history with TM and/or the existence of review processes specific to TM. TM-related regulatory changes that were enacted between the years 2000 and 2022 were identified and categorized into special departments, changes in clinical trials, or specialized tracks. The impact of these TM policies was measured via the number of TM-related INDs, approved applications, marketed drugs, and rejected applications per decade since 2000. This data was then organized alongside policies to draw conclusions about the influence of these regulatory changes. All data was collected using official government websites and journals published by independent, external research institutions accessed via USC’s library services. Results/Anticipated Results: Previous research revealed each country made efforts to integrate TMs into existing drug practices, such as clinical trials and safety requirements, although the extent and methods for the integration differed. Countries with a longer history with TMs are predicted to have regulatory systems that are more accommodating to the unconventional nature of TMs, making the approval and marketing of TMs much easier in these countries. As TM-related policies are more refined and increase in number in a given country, the number of TM-related applications and TMs marketed as legitimate, prescribable medications will also increase. Discussion/Significance of Impact: Timelines and charts displaying the impact of new TM-related regulatory changes will help identify a successful model for increasing TM IND submissions, approvals, and marketed TM drugs.